2002
DOI: 10.1046/j.1365-2818.2002.01077.x
|View full text |Cite
|
Sign up to set email alerts
|

Electron and light microscopy studies on the domain structures of Zn3B7O13Cl, Zn3B7O13Br and Zn3B7O13I ferroic boracites

Abstract: SummaryThe domain structures of Zn 3 B 7 O 13 Cl, Zn 3 B 7 O 13 Br and Zn 3 B 7 O 13 I boracite single crystals were studied by means of polarized light in conjunction with electron microscopy. Single crystals of the three compositions were grown by chemical transport reactions in closed quartz ampoules, at a temperature of 900 ° C and were examined by polarizing optical microscopy (PLM), scanning electron microscopy (SEM) and transmission electron microscopy (TEM). For both PLM and SEM, the same as-grown samp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
6
0

Year Published

2005
2005
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 34 publications
0
6
0
Order By: Relevance
“…For related structures, see: Mao et al (1991); Dowty & Clark (1972, 1973; Mendoza-Alvarez et al (1985); Schindler & Hawthorne (1998); Knorr et al (2007). For properties and potential applications of boracites, see: Campa-Molina et al (1994, 2002; Dana (1951); Mathews et al (1997); Smart & Moore (1992). For bond-valence parameters for oxides, see: Brese & O'Keeffe (1991).…”
Section: Related Literaturementioning
confidence: 99%
See 1 more Smart Citation
“…For related structures, see: Mao et al (1991); Dowty & Clark (1972, 1973; Mendoza-Alvarez et al (1985); Schindler & Hawthorne (1998); Knorr et al (2007). For properties and potential applications of boracites, see: Campa-Molina et al (1994, 2002; Dana (1951); Mathews et al (1997); Smart & Moore (1992). For bond-valence parameters for oxides, see: Brese & O'Keeffe (1991).…”
Section: Related Literaturementioning
confidence: 99%
“…detection (Campa -Molina et al, 1994, 2002 have been reported and in some sense, can be modulated by the presence of some specific types of cations. The aim of this research was to synthesize a new boracite with Zn and Fe in the crystalographic sites for Me in the general formula, in order to stablish in first instance, its structural and crystal chemistry properties.…”
Section: Data Collectionmentioning
confidence: 99%
“…T he unusual physical and chemical properties, such as ferroelectric, magnetic, dynamical, and structural properties 1 of boracites, M 3 B 7 O 13 X (M = divalent metals Mg, Cr, Mn, Fe, Co, Ni, Cu, Zn, Cd; X = usually Cl, Br, I), which represents a family of more than 25 isomorphous compounds, have been the focus of research for many years. 2 Usually, boracites have been prepared by four basic techniques, which include vaportransport-type methods, 3,4 sintering-flux-type methods, 5,6 sol− gel processes, 7 and hydrothermal methods. 8 In the vaportransport method, for example, HX and MX 2 acted as the gastransport agent, as indicated by the represented reactions listed below: 3 + = + MO 2HX(g) MX (g) H O(g) 2 2 Hydrothermal methods were used for many systems that discovered chalcogen, 8 hydroxyl, 8,9 and lithium boracites, 9 but they were not suitable for halogen boracites.…”
mentioning
confidence: 99%
“…2 Usually, boracites have been prepared by four basic techniques, which include vaportransport-type methods, 3,4 sintering-flux-type methods, 5,6 sol− gel processes, 7 and hydrothermal methods. 8 In the vaportransport method, for example, HX and MX 2 acted as the gastransport agent, as indicated by the represented reactions listed below: 3 + = + MO 2HX(g) MX (g) H O(g) 2 2 Hydrothermal methods were used for many systems that discovered chalcogen, 8 hydroxyl, 8,9 and lithium boracites, 9 but they were not suitable for halogen boracites.…”
mentioning
confidence: 99%
See 1 more Smart Citation